Incorporation studies of clickable ceramides in Jurkat cell plasma membranes. Issue 51 (9th June 2017) - Walter, T.; Schlegel, J.; Burgert, A.; Kurz, A.; Seibel, J.; Sauer, M.
Abstract : The acyl chain length and the azide position strongly influence the accessibility of the DBCO-dye, which was studied via TCEP quenching and anisotropy experiments. Abstract : The incorporation properties of ceramide analogues for click chemistry in Jurkat T cells were investigated. The analogues varied in the acyl chain length and the position of the functional group for click chemistry. Fluorescence microscopy studies including anisotropy and quenching experiments showed significant differences in the accessibility of the functional group indicating different incorporation properties into the plasma membrane.